Transformation of Islamic Religious Education in the Era of Digital Disruption Based on the Values of Religious Moderation - Rusli Takunas; Erniati; Andi Anirah; Ma'ruf (Journal of Contemporary Islamic Education, 2025)
The transformation of education in the era of digital disruption presents global challenges in the form of accelerated information flow, changes in learning patterns, and the increasing potential for the spread of extreme religious beliefs through the digital space. In the Indonesian national context, these conditions demand a strengthening of the role of Islamic Religious Education as a strategic instrument in shaping moderate, tolerant, and national value oriented religious characters. Therefore, a study of the transformation of Islamic Religious Education based on the value of religious moderation is important to ensure that the educational process remains relevant to technological developments while maintaining a balance of religious understanding. This study aims to analyze the concept and strategy of transforming Islamic Religious Education in the face of digital disruption by emphasizing the integration of the value of religious moderation in the learning process. The study uses a qualitative approach with a literature study type through the analysis of various books, scientific articles, and educational policy documents. Data collection techniques are carried out through documentation and library studies, while data analysis uses data reduction, thematic categorization, and conceptual interpretation with validity testing through source triangulation. The results of the study indicate that the transformation of Islamic Religious Education requires the integration of digital literacy, strengthening the value of religious moderation, and the development of reflective and contextual learning models. These findings have implications for strengthening the theoretical framework for curriculum development and adaptive and moderate learning practices.